Lúcio Yanel e o Violão Pampeano: memória(s), história(s) e identidade(s) de um fazer musical no sul do Brasil - Santos, José Daniel Telles dos (2012)
This study aims initially to register and analyze the life history of the Argentinian guitarist Lúcio Yanel (1946), as well as his artistic production in the last three decades in Rio Grande do Sul. This region s social and musical practices evoke reflections on the social memory, history, identity and tradition related to cultural phenomena such as native music festivals and the identity-cultural processes in the state. The guitarist style, which Yanel carries, is presented through reflections on the musical characteristics of this guitar, which is sometimes called Pampeano, from the analysis of a musical interpretation of the guitarist. Considering the production and work of this artist, some discussions have been raised from the reports of other guitarists about the possible formation of a guitar school connectedto the music of the Pampas in the state of Rio Grande do Sul. Through oral history, documental research and musical analysis, part of the life story of Lúcio Yanel acquires a new registration in this research that aims to contribute to discussion and analysis of socio-musical practices in Rio Grande do Sul, especially those connected to pampeanomusic and regional guitar